2018
DOI: 10.1186/s12913-018-2933-0
|View full text |Cite
|
Sign up to set email alerts
|

“Factors associated with non-small cell lung cancer treatment costs in a Brazilian public hospital”

Abstract: BackgroundThe present study estimated the cost of advanced non-small cell lung cancer care for a cohort of 251 patients enrolled in a Brazilian public hospital and identified factors associated with the cost of treating the disease, considering sociodemographic, clinical and behavioral characteristics of patients, service utilization patterns and survival time.MethodsEstimates were obtained from the survey of direct medical cost per patient from the hospital’s perspective. Data was collected from medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
0
2
1
Order By: Relevance
“…11 A chart review study of hospital-based costs from Brazil, however, suggested an effect of ECOG PS = 2 leading to lower total costs, which were potentially due to delayed rather than avoided costs. 12 ISC-IASLC disease stage was not a significant predictor in our study, potentially due to the study being restricted to patients with stage IIIB/IVaNSCLC, but was found a significant predictor in other chart reviews. 12,13 It may be that ISC-IASLC disease stage impacts indirect costs 14 or that ECOG PS was not included as an independent variable in these studies.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…11 A chart review study of hospital-based costs from Brazil, however, suggested an effect of ECOG PS = 2 leading to lower total costs, which were potentially due to delayed rather than avoided costs. 12 ISC-IASLC disease stage was not a significant predictor in our study, potentially due to the study being restricted to patients with stage IIIB/IVaNSCLC, but was found a significant predictor in other chart reviews. 12,13 It may be that ISC-IASLC disease stage impacts indirect costs 14 or that ECOG PS was not included as an independent variable in these studies.…”
Section: Discussioncontrasting
confidence: 68%
“…12 ISC-IASLC disease stage was not a significant predictor in our study, potentially due to the study being restricted to patients with stage IIIB/IVaNSCLC, but was found a significant predictor in other chart reviews. 12,13 It may be that ISC-IASLC disease stage impacts indirect costs 14 or that ECOG PS was not included as an independent variable in these studies. While other studies identified alcohol abuse as a prognostic factor for higher HCRU costs, it was correlated with significantly lower costs (total and per patient-month) in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…O tratamento oncológico apresenta alto custo em comparação com os demais tratamentos oferecidos pelo SUS. Estudo realizado por Barros Reis 10 demonstrou que o custo médio do tratamento oncológico no Brasil girou em torno de US$ 3.796,00 por paciente em 2011, sendo que 30% estão relacionados a internações hospitalares, e o restante abrange procedimentos ambulatoriais. Em levantamento sobre custos do tratamento do câncer cervical nos serviços públicos em 2006, Novaes et al 11 observaram que, de um montante de US$ 104.966.045, cerca de 8% foram destinados a internações clínicas.…”
unclassified